Altered resting state functional connectivity in early course schizophrenia. (30th January 2018) - Sharma, Aastha; Kumar, Arvind; Singh, Sadhana; Bhatia, Triptish; Beniwal, R.P.; Khushu, Subash; Prasad, Konasale M.; Deshpande, Smita N.
Abstract: Impaired connectivity is proposed to underlie pathophysiology of schizophrenia. Existing studies on functional connectivity show inconsistent results. We examined functional connectivity in a clinically homogenous sample of 34 early course schizophrenia patients compared with/to 19 healthy controls using resting state functional magnetic resonance imaging (rsfMRI). Mean duration of illness for schizophrenia patients was 4 ± 1.78 years. Following a comprehensive clinical assessment, rsfMRI data were acquired using a 3.0 T magnetic resonance imaging scanner, and analyzed using FSL version 5.01 software (FMRIB's Software Library, www.fmrib.ox.ac.uk/fsl ). Compared to healthy controls, schizophrenia patients had significantly decreased functional connectivity in the left fronto-parietal network, lateral and medial visual network, motor network, default mode network and auditory network. Our data suggests significant functional hypoconnectivity in selected brain networks in early schizophrenia patients compared to controls. It is likely that the observed functional hypoconnectivity may be associated with features of schizophrenia other than those examined in this study. It is possible that hypoconnectivity is necessary but not sufficient to the clinical manifestation of schizophrenia. The examination of functional connectivity as a biomarker should be extended to a wider array of disease phenotypes to better understand its significance. Highlights: Functional hypoconnectivity in selected brain networks in early schizophrenia. Hypoconnectivity in lateral & medial visual; motor, auditory and default mode networks. This is important but not sufficient to clinical manifestation of schizophrenia.